2019
DOI: 10.1017/s0047279419000941
|View full text |Cite
|
Sign up to set email alerts
|

Locked-in or Locked-out: Can a Public Services Market Really Change?

Abstract: Australia's welfare-to-work system has been subject to ongoing political contestation and policy reform since the s. In this paper we take a big picture look at the Australian system over time, re-visiting our earlier analysis of the impact of marketisation on flexibility at the frontline over the first ten years of the Australian market in employment services. That analysis demonstrated that marketisation had failed to deliver the service flexibility intended through contracting-out, and had instead produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Work on institutional change theory in public administration shows that the institutional norms and informal rules within roles can become intractable (Mahoney & Thelan, 2010). Considine, O'Sullivan, Mcgann, et al (2019) observed that subsequent reforms to employment services unsuccessfully attempted to address inflexibility by street level bureaucrats, caving to isomorphic pressures to return to previous inflexible working practices. The NDIS has been functioning nationally for just 2 years but soon the practices of local area coordinators may become fixed; shifting to a working culture of further support for participant's implementation and market shaping activities may prove challenging if action to return local area coordinators to their original role is not taken soon.…”
Section: Discussionmentioning
confidence: 99%
“…Work on institutional change theory in public administration shows that the institutional norms and informal rules within roles can become intractable (Mahoney & Thelan, 2010). Considine, O'Sullivan, Mcgann, et al (2019) observed that subsequent reforms to employment services unsuccessfully attempted to address inflexibility by street level bureaucrats, caving to isomorphic pressures to return to previous inflexible working practices. The NDIS has been functioning nationally for just 2 years but soon the practices of local area coordinators may become fixed; shifting to a working culture of further support for participant's implementation and market shaping activities may prove challenging if action to return local area coordinators to their original role is not taken soon.…”
Section: Discussionmentioning
confidence: 99%
“…Brodkin 2011; Jordan 2018). Relying on frontline workers' self‐reported experiences may be subject to some recall bias and the risk that respondents will over‐estimate their own agency as workers (see Considine et al 2019). Nevertheless, we do not consider this to be a major issue.…”
Section: Discussionmentioning
confidence: 99%
“…As stated, the main benefits would be an effective way of management, efficiency, consumer choice and cost effectiveness particularly through competition (Van Berke et al, 2012: 263;Bonvin, 2008: 372). Welfare markets in general and activation markets in particular are not conventional markets, they are mainly quasi markets (Considine et al, 2019;Van Berkel et al, 2012a;Considine et al 2011;Van Berkel and Borghi, 2008;Bredgaard and Larsen, 2007;Considine and Lewis, 2003). Bredgaard and Larsen (2007: 289) underline that "the principal idea is to create free market for employment services in which (primarily private) service providers bid in an open competition by public tendering.…”
Section: Marketization Contractualism and Quasi Marketsmentioning
confidence: 99%